(untitled) (ABUJA JOURNAL OF BUSINESS AND MANAGEMENT, 2024)
This study aimed to examine the effect of social media marketing, specifically through Facebook and Instagram, on the business success of beverage industry: a study of CWAY Food and Beverages Company Limited. The primary objectives were to assess the effect of Facebook usage on the company’s market share and to determine the impact of Instagram usage on the company’s imarket share and innovation. A cross-sectional survey design was employed, targeting a population of 144 staff members of CWAY food and Beverages Company Limited. A sample of 124 respondents was selected using simple random sampling. Data were collected through a structured questionnaire, which was validated by experts in the field to ensure content validity. The reliability of the instrument was confirmed using Cronbach's alpha, yielding a coefficient of 0.85, indicating high internal consistency. Data analysis was conducted using multiple regression analysis to test the hypotheses. The findings revealed a significant positive effect of social media marketing and business success. Specifically, Facebook usage had a substantial positive effect on the market share of CWAY food and beverages company limited, with a Beta value of 0.452 and a t-value of 9.456 (p < 0.05). Similarly, Instagram usage significantly influenced innovation, with a Beta value of 1.379 and a t-value of 28.844 (p < 0.05). The overall model was strong, with an R² value of 0.938, indicating that the usage of Facebook and Instagram explained 93.8% of the variance in business success. In conclusion, the study highlights the critical role of social media platforms, particularly Facebook and Instagram, in enhancing market share and driving innovation. The study recommends that CWAY Food and Beverages Company Limited continue to integrate Facebook into its marketing strategy to expand market reach, while also leveraging Instagram creative features to foster a culture of innovation and maintain competitive advantage in the beverage industry.